Social Innovation of Tubanan Agrocycleforestry: Community-Based Empowerment Practices for Sustainable Agriculture - Wahyu Mahaputra; Ahmad Ilham; A. Khoirul Anam; Miftah Arifin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Social innovation is often considered to have great potential to encourage sustainable development and transformation towards more sustainable economic practices. Many companies in preparing community empowerment programs with an orientation that is simply considered good at the start, even just to meet the interests of certain parties, but do not plan what benefits are targeted so that they quickly become obsolete. In order not to be left behind, companies must form a business model, embrace many parties, create sustainable programs from year to year, and prepare an exit strategy carefully. This article discusses social innovation practices in the PT PLN UIK Tanjung Jati B TJSL program based on the social innovation process model and empirical practice. This article contributes to improving the concept of social innovation, how social innovation succeeds and what factors encourage its emergence and growth.